Selective Chemical Labeling and Sequencing of 5-Hydroxymethylcytosine in DNA at Single-Base Resolution - Xiaogang Li (Frontiers Media S.A., 2021)
5-Hydroxymethylcytosine (5hmC), the oxidative product of 5-methylcytosine (5mC) catalyzed by ten-eleven translocation enzymes, plays an important role in many biological processes as an epigenetic mediator. Prior studies have shown that 5hmC can be selectively labeled with chemically modified glucose moieties and enriched using click chemistry with biotin affinity approaches. Besides, DNA deaminases of the AID/APOBEC family can discriminate modified 5hmC bases from cytosine (C) or 5mC. Herein, we developed a method based on embryonic stem cell (ESC) whole-genome analysis, which could enrich 5hmC-containing DNA by selective chemical labeling and locate 5hmC sites at single-base resolution with enzyme-based deamination. The combination experimental design is an extension of previous methods, and we hope that this cost-effective single-base resolution 5hmC sequencing method could be used to promote the mechanism and diagnosis research of 5hmC.